Calibration of Herbicide Applicators - Jason A. Ferrell; Brent A. Sellers (EDIS, 2009)
Revised! SS-AGR-102, a 3-page illustrated fact sheet by J.A. Ferrell and B.A. Sellers, describes two common methods for sprayer calibration, the 5940 method and the 1/128th acre method. Published by the UF Department of Agronomy, October 2009.